Development and implementation of a prescription opioid registry across diverse health systems. Issue 2 (17th May 2022) - Ray, G Thomas; Altschuler, Andrea; Karmali, Ruchir; Binswanger, Ingrid; Glanz, Jason M; Clarke, Christina L; Ahmedani, Brian; Andrade, Susan E; Boscarino, Joseph A; Clark, Robin E; Haller, Irina V; Hechter, Rulin; et al.
Abstract: Objective: Develop and implement a prescription opioid registry in 10 diverse health systems across the US and describe trends in prescribed opioids between 2012 and 2018. Materials and Methods: Using electronic health record and claims data, we identified patients who had an outpatient fill for any prescription opioid, and/or an opioid use disorder diagnosis, between January 1, 2012 and December 31, 2018. The registry contains distributed files of prescription opioids, benzodiazepines and other select medications, opioid antagonists, clinical diagnoses, procedures, health services utilization, and health plan membership. Rates of outpatient opioid fills over the study period, standardized to health system demographic distributions, are described by age, gender, and race/ethnicity among members without cancer. Results: The registry includes 6 249 710 patients and over 40 million outpatient opioid fills. For the combined registry population, opioid fills declined from a high of 0.718 per member-year in 2013 to 0.478 in 2018, and morphine milligram equivalents (MMEs) per fill declined from 985 MMEs per fill in 2012 to 758 MMEs in 2018. MMEs per member declined from 692 MMEs per member in 2012 to 362 MMEs per member in 2018. Conclusion: This study established a population-based opioid registry across 10 diverse health systems that can be used to address questions related to opioid use. Initial analyses showed large reductions in overall opioid use per member among the combined health systems. The registry will be used in future studies to answer a broad range of other critical public health issues relating to prescription opioid use. Lay Summary: Prescription opioid use has played a large role in the opioid crisis over the last 2 decades. This article describes the development and implementation of a population-based prescription opioid registry using electronic health record and claims data from 10 diverse health systems in the United States. We also conduct descriptive analyses of opioid use trends over the study period of January 1, 2012–December 31, 2018. Patients who filled a prescription for an opioid, and/or had an opioid use disorder diagnosis in the study period are included in the registry. The registry contains several data domains: patient demographics, medications, including prescription opioids and benzodiazepines, clinical diagnoses, health procedures, health services utilization, health plan membership, and mortality. The registry includes 6 249 710 patients and over 40 million outpatient opioid fills. Descriptive analyses showed large reductions in overall opioid use per member among the combined health systems over the study period. The registry is a large, comprehensive data resource with a flexible data structure that can be leveraged in future studies to answer a broad range of critical public health questions relating to prescription opioid use. The design may be useful for other research teams developing similar data resources.